2003
DOI: 10.1103/physreve.68.021301
|View full text |Cite
|
Sign up to set email alerts
|

Partially fluidized shear granular flows: Continuum theory and molecular dynamics simulations

Abstract: The continuum theory of partially fluidized shear granular flows is tested and calibrated using two dimensional soft particle molecular dynamics simulations. The theory is based on the relaxational dynamics of the order parameter that describes the transition between static and flowing regimes of granular material. We define the order parameter as a fraction of static contacts among all contacts between particles. We also propose and verify by direct simulations the constitutive relation based on the splitting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 38 publications
(92 reference statements)
3
119
3
Order By: Relevance
“…We hypothesize that to accurately capture the dynamics we have observed (including fluctuations and stopping acceleration), the physics of rapid fluidization and solidification must be included. Beyond discrete simulations [4], multi-phase modelling like that proposed in [28] might be applicable or perhaps such features will have to be captured by statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that to accurately capture the dynamics we have observed (including fluctuations and stopping acceleration), the physics of rapid fluidization and solidification must be included. Beyond discrete simulations [4], multi-phase modelling like that proposed in [28] might be applicable or perhaps such features will have to be captured by statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical models try to take into account the existence of this contact network through different approaches. Some models describe the flow as a mixture of solid and liquid phases [5] or try to account for the frictional contacts by adding a frictional term in collisional theories [6,7]. Other models consider the presence of arches in the flow [8,9] or account for some non local propagation of momentum through the contact network [10,11].…”
mentioning
confidence: 99%
“…In initial studies with weak dissipation and dynamic friction [26] near φ rcp , we found that t l is similar to that for systems with dissipation and no dynamic friction. However, more extensive studies of dynamic as well as static friction are required to make a definitive statement about the influence of friction on the long-time stability of nonlinear velocity profiles [11,12]. Second, most experimental studies of velocity profiles in granular systems are performed in (angular) Couette, not planar shear cells.…”
Section: Future Directionsmentioning
confidence: 99%
“…Thus, molecular dynamics simulations are often employed to study dense granular shear flows, for example in Refs. [10,11,12,13]. We choose a similar plan of attack and perform molecular dynamics simulations of model frictionless dense granular systems undergoing boundary-driven planar shear flow in 2D.…”
Section: Introductionmentioning
confidence: 99%